2015
DOI: 10.1080/10586458.2015.1005853
|View full text |Cite
|
Sign up to set email alerts
|

Random Sampling of Trivial Words in Finitely Presented Groups

Abstract: We describe a novel algorithm for random sampling of freely reduced words equal to the identity in a finitely presented group. The algorithm is based on Metropolis Monte Carlo sampling. The algorithm samples from a stretched Boltzmann distributionwhere |w| is the length of a word w, α and β are parameters of the algorithm, and Z is a normalising constant. It follows that words of the same length are sampled with the same probability. The distribution can be expressed in terms of the cogrowth series of the grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…In [5] a numerical method was used to find bounds for the cogrowth of groups, and a lower bound for the cogrowth rate of BS(N, M ) for small values of N, M were computed. A significant improvement of this numerical work has been undertaken by the authors, which can be found in [4].…”
Section: Introductionmentioning
confidence: 99%
“…In [5] a numerical method was used to find bounds for the cogrowth of groups, and a lower bound for the cogrowth rate of BS(N, M ) for small values of N, M were computed. A significant improvement of this numerical work has been undertaken by the authors, which can be found in [4].…”
Section: Introductionmentioning
confidence: 99%
“…Extrapolations of our computational results suggest the same as our previous paper, namely, that F might not be amenable. A recent experimental work by Elder, Rechnitzer and Janse van Reusburg [7] on the amenability problem of F using statistical methods arrives also to the same conclusion that F might be non-amenable (see also [8]). As in [10,Section 2], by the norm of ||a|| of an element a in the group ring of a discrete group Γ we mean…”
Section: Introductionmentioning
confidence: 70%
“…(8), (9); the idea is the following: Since (ab) n = Cb(ab) n + C −1 b(ab) n , and b(ab) n is self-adjoint, we can obtain the terms of the expanded sum for C −1 b(ab) n from those of Cb(ab) n by using the "reverse-inverse" map π • J = Ad(D 2 )•R given in Eq. (7). For instance the reverse-inverse of the word CDC 2 D 2 is D 2 R(CDC 2 D 2 ) D 2 = C −1 D −1 C −2 D −2 , which corresponds to reversing the order of the letters and taking the inverse.…”
Section: Resultsmentioning
confidence: 99%
“…[7,3,12,14,13]). Our paper is the first that considers the moments of T * 1 T 1 for T 1 := I + A+ B.…”
Section: Moreover In Both Cases the Upper Bound Is Attained If And Omentioning
confidence: 99%